What can be achieved through education at all? A response to Julian Culp. Issue 3 (4th December 2020) - Geiss, Michael
ABSTRACT: In the following I would like to expose Julian Culp's normative argumentation to some empirical considerations. My commentary focuses on one of the central premises of the book: Culp assumes that education can make a decisive contribution to solving the current challenges in plural and globalized societies. He states that recent political philosophy has unacceptably neglected the issue of education. But the book's aim is not the theoretical determination of education itself. Rather, Culp is concerned with the question of giving education the right normative foundation to solve the social, ecological and democratic challenges the globalized world is currently facing. I don't think that one can or should discuss and analyse education without normative considerations. Educational thinking cannot do without a normative foundation and it is helpful and necessary to reflect upon them philosophically. This is the central concern of the book, and there is nothing to be added to it by historians or educational researchers. But a purely normative approach runs the risk of repeating many of the problems inherent in educational thinking. I think that even a normative approach would gain a lot from taking the empirical and historical boundaries of its subject more seriously than Culp does. Therefore, most of my remarks are about the relationship between normative theory and historical realities.